Clinical-pathological characteristics and management of primary tumors of the small intestine of jejuno-ileal location - Paredes Méndez, Juan Eloy (2021)
Introduction: Primary tumors of the small intestine (PTID) represent approximately 5% of all primary gastrointestinal neoplasms; the latter include benign and malignant lesions, with different histological subtypes. Objective: To describe the clinical-pathological characteristics and the management of tumors located in the jejunum-ileum. Materials and methods: A descriptive, retrospective study was carried out in a single center. Results: 45 patients were included, the average age at diagnosis was 54.2 ± 8.2 years. 27 were male (60%). In the diagnostic algorithm, computed tomography was used in all patients, double-balloon enteroscopy in 41 (91.1%) and video capsule endoscopy in 32 (71.1%). Endoscopic procedures such as: biopsies, tattoos, resection and dilation were performed in 40 (88.9%), 39 (86.7%), 4 (8.9%) and 1 (2.2%) patients, respectively. The most frequent location was the jejunum in 39 (86%). GIST was confirmed in 18 (40%), followed by lymphoma in 16 (35.6%) and adenocarcinoma in 5 (11%) cases. All GIST, adenocarcinoma, and neuroendocrine tumors underwent surgical treatment and chemotherapy; treatment of lymphomas consisted mainly of combined treatment; three harmartomas and one fibroangiolipoma were resected endoscopically. Conclusions: The most frequent jejunoileal small intestine tumors were GISTs, followed by lymphomas and adenocarcinomas. Double-balloon enteroscopy was the main diagnostic and therapeutic tool.